Модель статистичної мультифрагментації в рамках розширеного підходу морфологічної термодинаміки - Kucherenko, V.S.; Bugaev, K.A.; Sagun, V.; Ivanytskyi, O. (Publishing house "Academperiodika", 2022)
On the basis of the morphological thermodynamics, we develop an exactly solvable version of the statistical multifragmentation model for the nuclear liquid-gas phase transition. It is shown that the hard-core repulsion between spherical nuclei generates only the bulk (volume), surface, and curvature parts of the free energy of the nucleus, while the Gaussian curvature one does not appear in the derivation. The phase diagram of the nuclear liquid-gas phase transition is studied for a truncated version of the developed model.